Integrative Curriculum Management in Shaping Muslim Character in Pesantren - Muhammad Yusuf; Nur Ali; Muhammad Amin Nur (Ta'dib, 2023)
This research aims to describe the implementation of integrative curriculum management in shaping the Muslim character of Pesantren Mahasiswa Al Hikam, Malang. This research used a qualitative approach. Data collection method was conducted by means of interviews, observation and documentation. Data analysis used the interactive analysis model of Miles and Huberman. The results of the study found that 1) The concept of integrative curriculum management was very innovative, because it followed the times by linking academics with student life; 2) The implementation of integrative curriculum management in shaping Muslim character referred to the formulation of philosophy which was then integrated into three institutions, dirosah, learning section, santrian that handlee santri by making scientific works created by teachers and students; and 3) The implications of integrative curriculum management in shaping Muslim character could be seen in positive habits formed in pesantren, such as keeping congregational prayers, reading the Qur'an, and gaining religious knowledge that can be applied on campus. Based on formal findings, the pesantren applied a curriculum that integrated theory and practice in a comprehensive system in which Dirosah became the main teaching aspect.